2013
DOI: 10.1016/j.bbadis.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of extracellular matrix in periodontitis: Gingipains differentially affect cell adhesion activities of fibronectin and tenascin-C

Abstract: Gingipains are cysteine proteases that represent major virulence factors of the periodontopathogenic bacterium Porphyromonas gingivalis. Gingipains are reported to degrade extracellular matrix (ECM) of periodontal tissues, leading to tissue destruction and apoptosis. The exact mechanism is not known, however. Fibronectin and tenascin-C are pericellular ECM glycoproteins present in periodontal tissues. Whereas fibronectin mediates fibroblast adhesion, tenascin-C binds to fibronectin and inhibits its cell-spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 59 publications
(91 reference statements)
3
39
0
Order By: Relevance
“…Fragments of tenascin-C have been reported in swabs from individuals with gingivitis, 189 chronic venous leg ulcer exudates, 164 and atherosclerotic plaques 190 among other locations.…”
Section: Assembly Of Tenascin-c Into a Fibrillar Matrixmentioning
confidence: 99%
“…Fragments of tenascin-C have been reported in swabs from individuals with gingivitis, 189 chronic venous leg ulcer exudates, 164 and atherosclerotic plaques 190 among other locations.…”
Section: Assembly Of Tenascin-c Into a Fibrillar Matrixmentioning
confidence: 99%
“…Finally, tenascin-C can be cleaved by matrix metalloproteases (MMPs) (Giblin and Midwood, 2015) and gingipain cysteine proteases (Ruggiero et al, 2013), which contributes to tenascin-C turnover in tissue. In vitro cleavage of purified tenascin-C through MMP-1,-2, -3 and -7 demonstrated that the majority of cleavage sites are located within the alternatively spliced domains, although MMP-7 and the proteinase ADAMTS5 (a disintegrin and metalloproteinase with thrombospondin motifs 5) both also cleave within the assembly domain.…”
Section: Box 1 the Evolution Of Tenascin-cmentioning
confidence: 99%
“…This differential affinity towards fibronectin is most likely due to the presence of the hemaglutinin domains in the HRgpA complex, which bind fibronectin facilitating proteolytic fragmentation. Our results of HRgpA dependent fibronectin fragmentation are consistent with the results of Ruggiero and others [108]. The presence of the hemaglutinin adhesion domain may serve as an important anchoring device to the extracellular milieu within the periodontal pocket.…”
Section: Gingipains Stimulate Fibroblasts To Produce a Pro-inflammatosupporting
confidence: 82%
“…P. gingivalis use its gingipains to proteolytically cleave integrin-gingipains interactions on fibroblast cell surface [107]. Previous studies demonstrate that gingival fibroblasts when cocultured with a high concentration of purified gingipains lead to a decrease in fibronectin and α5β1 integrin, causing cell detachment and cell death [108]. Not surprisingly, samples taken from patients with periodontitis demonstrated increased amounts of fibronectin fragments, the result of host and pathogen proteolysis [109,110].…”
Section: Figure 8 the Behavior Of Individual Cells And The Dynamic Smentioning
confidence: 99%